2022
DOI: 10.3390/biom12030419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Intrauterine Dose of Human Recombinant Galectin-1 Buffered on Pregnancy Rate in Inseminated Cows

Abstract: The objective was to evaluate the efficacy of a single dose of exogenous galectin-1 in improving the pregnancy rate in inseminated cows, comparing the pregnancy rate of the two groups (treatment and control Groups) into 107 contemporary groups (YG) established. An ultrasound exam determined the pregnancy rate performed 25 to 35 days after the fixed-time artificial insemination (FTAI) of breeding beef cows (n = 3469). The pregnancy rate of cows that received a single dose of eGAL-1 (200 ± 10 µg), with an intrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…There are so many particularities between placentation and embryo elongation of different mammals' species but, based on [20,21,22], that described that GAL-1 has a high degree of structural conservation, dimerization, and binding properties with carbohydrates and integrins (adhesion proteins), suggesting that these properties are conserved among vertebrates and that they maintain a pattern of gene expression among the different types of the placenta (deciduous or not), supported the decision to use a human gene to produce the recombinant protein for other species. Previous studies have demonstrated the biological functionality of rHGAL-1 to improve the pregnancy rate in cows, suggesting the potential use in other species [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are so many particularities between placentation and embryo elongation of different mammals' species but, based on [20,21,22], that described that GAL-1 has a high degree of structural conservation, dimerization, and binding properties with carbohydrates and integrins (adhesion proteins), suggesting that these properties are conserved among vertebrates and that they maintain a pattern of gene expression among the different types of the placenta (deciduous or not), supported the decision to use a human gene to produce the recombinant protein for other species. Previous studies have demonstrated the biological functionality of rHGAL-1 to improve the pregnancy rate in cows, suggesting the potential use in other species [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that blockage of GAL-1-mediated angiogenesis or lectin can disturb the processes associated with good placentation. Data from the authors (the improvement of the amount of GAL-1 into the bovine uterus) can be cited as a good example of impact of this protein in the pregnancy rate (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations